Time Course and Risk Factors for Myocardial Dysfunction After Aneurysmal Subarachnoid Hemorrhage. Issue 6 (June 2015) - van der Bilt, Ivo A.; Hasan, Djo; van den Brink, Renee B.; Cramer, Maarten J.; van der Jagt, Mathieu; van Kooten, Fop; Regtien, Joost G.; van den Berg, Maarten P.; Groen, Rob J.; Cate, Folkert J. ten; Kamp, Otto; Götte, Marco J.; et al.
Abstract : BACKGROUND: Myocardial wall motion abnormalities (WMAs) are independent risk factors for a poor outcome in patients with aneurysmal subarachnoid hemorrhage (aSAH). OBJECTIVE: To study the time course of WMAs during the initial phase after aSAH and to investigate which clinical, electrocardiographic, or myocardial serum markers are predictors of early or late development of WMAs. METHODS: In a prospective, multicenter cohort study in patients with aSAH, we performed serial electrocardiography and echocardiography and measured troponin T and N-terminal pro–B-type natriuretic peptide. WMAs present on admission were considered early WMAs; those that developed during the clinical course were considered late WMAs. Using multivariable regression analysis, we calculated odds ratios with corresponding 95% confidence intervals for clinical parameters, electrocardiography, and myocardial serum makers with early or late occurrence of WMAs. RESULTS: We included 301 patients (mean age ± SD, 57 ± 13) years. Multivariable odds ratios for early WMAs were poor clinical condition, 2.7 (95% confidence interval: 1.1-6.8); sinus tachycardia, 5.0 (1.3-19.9); ST-segment depression, 3.7 (1.02-13.1); ST-segment elevation, 16.6 (1.5-178.9); and increased troponin T, 2.8 (1.1-7.3). Multivariable odds ratios (95% confidence intervals) for late development of WMAs were 6.8 (1.6-30) for a myocardial infarct pattern on admission electrocardiography and 3.4 (1.4-8.5) for increased troponin T on admission. CONCLUSION: WMAs may be present on admission or develop during the course of aSAH. Poor neurological condition on admission, sinus tachycardia, ST-segment depression, and ST-segment elevation on admission electrocardiography and increased troponin T are independent predictors of early WMAs; a myocardial infarct pattern on admission ECG and increased troponin T independently predict late WMAs. CLINICAL TRIAL REGISTRATION: NCT00123695. ABBREVIATIONS: aSAH, aneurysmal subarachnoid hemorrhage CI, confidence interval ECG, electrocardiography OR, odds ratio WMA, wall motion abnormality